Ulama dalam Politik Pemilu pada Pemilihan Gubernur DKI Jakarta 2017 - Afif Ginanjar; Ari Ganjar Herdiansah; R. Widya Setiabudi Sumadinata (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study analyzes the factors of interest in the involvement of ulama in electoral politics by taking the case of the support of the Ulama and Habaib Forum (FUHAB) against Anies-Sandi in the DKI Jakarta Regional Head Election (Pilkada) 2017. The research method used is qualitative with the technique of collecting interview data with the FUHAB figures, Anies-Sani's success team, politicians, and academics as well as a literature review. The results showed that the dimensions of the interests which were arranged in the form of the economy of the ummah were based on identity. They strongly perceive some of the programs offered by Anies-Sandi as pro-people represented by the urban poor, such as stopping reclamation. In a practical manner, the political support of the FUHAB was fluid because in the early rounds they supported Agus-Silvi. The forms of their political work included using recitation and khutbah jum'at as well as securing votes at lower levels in the voting process. After Anies-Sandi won, the Habaib Ulama Forum (Fuhab), like other organizations, then received grant funds from the government and this shows that civil society organizations have a political bargaining position in elections which is useful for their interests.